Polysulfone resin as well as preparation method and application thereof
By adjusting the types and addition methods of inorganic salt catalysts, controlling the molecular weight distribution of polysulfone resins, the problem of difficulty in reducing the content of ring-shaped dimers in the prior art is solved, and the heat resistance and yellowing resistance of polysulfone resins are improved. It also improves solution stability and is suitable for the preparation of high-performance materials.
Patent Information
- Application Number
- CN202411578359.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-07
AI Technical Summary
In the existing polysulfone resin preparation process, the content of cyclic dimers is difficult to effectively reduce, resulting in limited improvement in solution stability, and the use of inorganic salt catalysts affects the uneven polymerization reaction, resulting in excessive proportions of ultra-high molecular weight and ultra-low molecular weight. , affects the heat resistance and yellowing resistance of the material.
By changing the types and addition methods of inorganic salt catalysts, polysulfone resins are prepared by nucleophilic substitution method to control the molecular weight distribution, so as to reduce the ratio of ultra-high molecular weight and ultra-low molecular weight, potassium acetate is used as part of the inorganic salt catalyst, and in the polymerization reaction Regulate its proportion and addition order to avoid local uneven reactions.
It has achieved narrowing of the molecular weight distribution in polysulfone resin, improved the heat resistance, yellowing resistance and solution stability of the material, and is suitable for water treatment and hemodialysis and other fields.
Smart Images

Figure BDA0005122371140000031 
Figure BDA0005122371140000032 
Figure BDA0005122371140000033
Abstract
Description
Technical Field
[0001] The invention relates to a polysulfone resin and a preparation method and application thereof, belonging to the technical field of polysulfone resins. Background Art
[0002] Polysulfone is a type of special engineering plastic with excellent comprehensive performance, which is widely used in the fields of electronics, aerospace, automobiles and medical treatment. In recent years, with the continuous development of science and technology, cutting-edge industries have also put forward higher requirements on the performance and stability of polysulfone materials.
[0003] Polysulfone resin is a slightly amber thermoplastic polymer with excellent mechanical and heat resistance properties. It can also resist high-temperature steam sterilization, so it can be used as medical trays, mouse cages, electrolytic cell structures, etc. At the same time, polysulfone is one of the main materials for water treatment membranes and hemodialysis membranes, and its solution stability is an important indicator for processing membrane materials.
[0004] Patent CN116003796B uses nucleophilic polycondensation-anionic ring-opening polymerization to prepare polysulfone resin. Organic borate-potassium biphenyl bisphenolate is added as an initiator. The obtained polysulfone resin has a low content of cyclic dimers, which is beneficial to the application of downstream products. However, the initiator is difficult to synthesize and will increase the impurity content. At the same time, the solution stability of the product is not evaluated.
[0005] Patent 116217932B uses an induced crystallization method to reduce the content of cyclic dimers in polysulfone. The cyclic dimer precipitates and crystallizes at a fast rate, and the prepared polysulfone has a low content of cyclic dimers, which improves the film-forming processing efficiency of the polysulfone material. However, the polymerization process is complicated, and only reducing the cyclic dimer content has a small effect on the improvement of solution stability.
[0006] The inventors of this patent have found that, except for cyclic dimers, the ratio of low molecular weight to ultra-high molecular weight in the polymer is a key factor affecting the stability of the solution, which can further improve the solution stability and increase the yellowing resistance and degradation resistance of the polymer.
[0007] In summary, it is necessary to prepare a polysulfone resin with a small proportion of oligomer content and polymer content from the perspective of polymerization process, so as to further improve the heat resistance and stability of the polysulfone material. Summary of the invention
[0008] The inventors have conducted a comprehensive study on the structure and properties of polysulfone resins, and found that the ultra-high molecular weight molecular structure and the ultra-low molecular weight structure in the polymer have a great influence on the performance of the polymer material. A high content of the ultra-low molecular weight part will greatly reduce the long-term heat resistance and yellowing resistance of the material, while the processing fluidity of the polymer in the ultra-high molecular weight part is poor. The higher the content, the more uneven mixing and even agglomeration will be caused during the polymer processing, which will lead to the problem of unstable solution performance of the prepared product.
[0009] The inventor has found through research that in the process of preparing polysulfone, the alkalinity, type and addition method of the inorganic salt catalyst have a great influence on the polymerization reaction rate. When the alkalinity of the inorganic salt is too strong, the polymerization activation energy is low, the speed is fast, the molecular weight growth is uneven, the low molecular weight and ultra-high molecular weight parts account for a large proportion, and the side reaction is serious; when the alkalinity of the inorganic salt is relatively weak, the polymerization speed is slow, the time is long, and it is easy to cause the problems of molecular weight not meeting the standard and low polymerization efficiency. At the same time, if the salt is added to the polymerization system all at once before the reaction, the solid content in the system is high, and the inorganic salt is easily agglomerated due to water absorption, resulting in excessively high local salt concentration in the system, thereby accelerating the polymerization rate of the nearby raw materials, resulting in a high proportion of ultra-high molecular weight parts in the product. The present invention avoids the above-mentioned problem of uneven reaction by changing the type and addition method of the inorganic salt catalyst, and the content of oligomers and polymers in the prepared polymer is significantly reduced, which can achieve the above-mentioned purpose, thereby completing the present invention.
[0010] An object of the present invention is to provide a polysulfone resin, which has a small proportion of ultra-high molecular weight molecular structures and ultra-low molecular weight molecular structures and a narrow molecular weight distribution, thereby having excellent heat resistance, yellowing resistance and solution stability.
[0011] Another object of the present invention is to provide a method for preparing the polysulfone resin.
[0012] Another object of the present invention is to provide a use of polysulfone resin with improved properties.
[0013] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solution:
[0014] A polysulfone resin is prepared by a nucleophilic substitution method using a para-dihalogen diphenyl sulfone compound of formula (I) and a bisphenol A-type compound of formula (II) as raw materials; and has the following structural characteristics: assuming that A is the logarithmic value log(M) of the molecular weight M, and B is dC / dlog(M) obtained by differentiating the concentration fraction C with the logarithmic value log(M) of the molecular weight, then in a molecular weight distribution curve with A as the horizontal coordinate and B as the vertical coordinate, (1) the value of B reaches a maximum in the range of 4.5≤A≤5.5, and (2) in the molecular weight distribution curve, the value obtained by integrating the B value in the range of A≤A-0.8 and A≥A+0.3 is 3%-10% relative to the value obtained by integrating the B value in the entire range of A;
[0015]
[0016] Wherein, R1, R2, R3, R4, R5, R6, R7, and R8 are independently selected from H, halogen, C1-C 10 Alkyl, C5-C6 cycloalkyl or C6-C 10 Any one of the aryl groups; X1 and X2 are selected from the same halogen.
[0017] In a specific embodiment, the structural formulas of the para-dihalogen diphenyl sulfone compound of formula (I) and the bisphenol A-type compound of formula (II) are respectively:
[0018]
[0019] In a preferred embodiment, the mass content of the cyclic dimer of the formula (V) in the polysulfone resin is less than 1.2%.
[0020]
[0021] On the other hand, a method for preparing the aforementioned polysulfone resin comprises the following steps:
[0022] (1) Preparation of composite inorganic salts: Weigh potassium acetate and other inorganic salts, crush them at high speed, mix them evenly and set aside;
[0023] (2) Polymerization reaction: first, the polymerization raw material monomer, organic solvent and part of the composite inorganic salt are added to the reaction kettle, and after nitrogen replacement, the temperature is raised to the boiling point of the solvent to separate water; as the salt formation reaction and water separation continue, the water content in the distilled liquid continues to decrease. When the water content in the system reaches the standard, the remaining composite inorganic salt is added and the reaction is continued. When the solution viscosity reaches the standard, the temperature is lowered to stop the reaction;
[0024] (3) Post-treatment: The polymer solution is diluted and filtered, and the filtrate is precipitated and crushed. Finally, the crushed powder is washed and dried to obtain the polysulfone resin.
[0025] In a specific embodiment, in the preparation of the composite inorganic salt, other types of inorganic salts may be one or more of K2CO3, KHCO3, Na2CO3 or NaHCO3.
[0026] In a specific embodiment, in the preparation of the composite inorganic salt, potassium acetate accounts for 5% to 50% of the molar amount of all inorganic salts, for example 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc., preferably 10% to 40%, more preferably 15% to 30%.
[0027] In a specific embodiment, in the preparation of the composite inorganic salt, after crushing by a high-speed crusher, the particle size D50 of the composite inorganic salt is below 100 μm, for example, 90 μm, 80 μm, 70 μm, 60 μm, 50 μm, 40 μm, 30 μm, 20 μm, 10 μm, etc., preferably below 70 μm, more preferably below 50 μm.
[0028] In a specific embodiment, in the polymerization reaction, the molar ratio of the para-dihalogen diphenyl sulfone compound of formula (I) and the bisphenol A-type compound of formula (II) in the polymerization raw monomers, preferably 4,4'-dichlorodiphenyl sulfone to bisphenol A is 1:(0.95-1.05), for example, 1:0.95, 1:0.96, 1:0.97, 1:0.98, 1:0.99, 1:1.0, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, etc., preferably 1:(0.97-1.03), and more preferably 1:(0.98-1.02).
[0029] In a specific embodiment, in the polymerization reaction, the organic solvent used is one or more of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or sulfolane.
[0030] In a specific embodiment, in the polymerization reaction, the mass fraction of the organic solvent used is 20% to 60%, for example, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, etc., preferably 25% to 55%, more preferably 30% to 50%.
[0031] In a specific embodiment, in the polymerization reaction, the molar amount of the composite inorganic salt used is 100% to 150% of the molar amount of the dihalogen diphenyl sulfone compound monomer, for example, 105%, 110%, 115%, 120%, 125%, 130%, 135%, 140%, 145%, 150%, etc., preferably 110% to 140%, and more preferably 120% to 130%.
[0032] In a specific embodiment, in the polymerization reaction, the part of the composite inorganic salt added in the early stage accounts for 40% to 70% of the total mass of the composite inorganic salt, for example 45%, 50%, 55%, 60%, 65%, 70%, etc., preferably 45% to 65%, more preferably 50% to 60%.
[0033] In a specific embodiment, in the polymerization reaction, the water content of the distillate reaches the standard of less than 2000 ppm, for example, 1900 ppm, 1800 ppm, 1700 ppm, 1600 ppm, 1500 ppm, 1400 ppm, 1300 ppm, 1200 ppm, 1100 ppm, 1000 ppm, 900 ppm, 800 ppm, 700 ppm, 600 ppm, 500 ppm, etc., preferably less than 1500 ppm, more preferably less than 1000 ppm, that is, the water content in the distillate is less than 2000 ppm, preferably less than 1500 ppm, more preferably less than 1000 ppm, which is regarded as the water content in the system reaching the standard.
[0034] In the present invention, the water content in the distillate can be tested by conventional methods in the art, for example, the quantitative distillate can be added to a Karl Fischer titrator to measure the water content by titration, without particular limitation. Similarly, the viscosity of the solution can also be tested by conventional methods in the art, for example, the viscosity of the reaction solution can be determined by the value of the stirring motor current, etc.
[0035] In the present invention, the post-treatment process of step (3) is not particularly limited and can be carried out with reference to the prior art. For example, the polysulfone resin can be obtained by filtering the polysulfone resin by means of a plate filter, a bag filter or a centrifugal filter, and then precipitating and crushing the filtrate with a poor solvent such as water, ethanol, methanol, etc., and finally washing the crushed powder with water and drying the powder.
[0036] On the other hand, the polysulfone resin or the polysulfone resin prepared by the above preparation method is used in the fields of squirrel cages, flow meters, hydrogen electrolyzers and hollow fiber membranes.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] The ultra-high molecular weight and ultra-low molecular weight contents of the polysulfone resin of the present invention meet specific ranges, so that the polysulfone resin has excellent heat resistance, yellowing resistance and degradation resistance.
[0039] The invention introduces potassium acetate as a partial inorganic salt catalyst in the polymerization process, and reduces the content of ultra-high molecular weight and ultra-low molecular weight in the product without reducing the polymerization rate by regulating the proportion of potassium acetate; and simultaneously avoids the problem of uneven local reaction by regulating the process, thereby preparing a polysulfone resin with low content of ultra-high molecular weight and ultra-low molecular weight, and the polysulfone resin has excellent heat resistance, yellowing resistance and degradation resistance. In addition, the organic solution containing the polysulfone resin of the invention has good stability and is more suitable for application in membrane making fields such as water treatment and hemodialysis. DETAILED DESCRIPTION
[0040] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.
[0041] The polysulfone resin of the present invention can be used to prepare any type of molded parts through molding processes such as injection molding, extrusion, casting, and blow molding.
[0042] Preferred applications of the polysulfone resins of the invention are transparent / translucent or colored injection moldings, extrudates such as sheets, film laminates, profiles, semi-finished products, and cast membranes or hollow fiber membranes made of high molecular weight bisphenol A type polysulfones.
[0043] The sources of raw materials used in the following examples and comparative examples are as follows:
[0044] Bisphenol A, Aladdin Reagent Co., Ltd., purity >99%;
[0045] 4,4'-Dichlorodiphenyl sulfone, Aladdin Reagent Co., Ltd., purity >98%;
[0046] N,N-dimethylacetamide, Aladdin Reagent Co., Ltd., purity >99%;
[0047] N,N-dimethylformamide, Aladdin Reagent Co., Ltd., purity >99%;
[0048] N-methylpyrrolidone, Aladdin Reagent Co., Ltd., purity >99%;
[0049] Potassium acetate, Aladdin Reagent Co., Ltd., purity >99%;
[0050] Potassium carbonate, Aladdin Reagent Co., Ltd., purity >99%.
[0051] The prepared polysulfone resin was tested for performance using the following method:
[0052] The molecular weight of the polymer is tested by gel permeation chromatography (GPC). The instrument model is Shimadzu LC-20ADXR, DMF is the mobile phase, PMMA is the standard sample, and the column temperature and the box temperature are both 40°C. The differential molecular weight distribution curve can be obtained by the following method. First, the time curve (elution curve) of the intensity distribution detected in the RI detector is made into a molecular weight distribution curve relative to the logarithmic value (log(M)) of the molecular weight using a standard curve. Then, after obtaining the integral molecular weight distribution curve relative to log(M) when the total area of the distribution curve is set to 100%, the integral molecular weight distribution curve is differentiated by log(M), thereby obtaining a differential molecular weight distribution curve relative to log(M). It should be noted that a series of operations until the differential molecular weight distribution curve is obtained can usually be performed using analysis software built into the GPC measurement device.
[0053] The heat resistance test requires that the dried pellets remain at 340°C in the injection molding machine for 10 minutes, and the samples before and after heat resistance are taken for yellowness index test. The test standard refers to ASTM E313, the sample thickness is 2mm, and the difference before and after heat resistance is calculated as the heat resistance yellowing variable.
[0054] The solution stability test requires that the polysulfone pellets be dissolved in a DMF solvent, with a polysulfone mass fraction of 25%. After dissolution, the solution is placed in a constant temperature environment of 25° C. for three days, and the turbidity of the solution is tested by a turbidity meter, the instrument model is LICO 620.
[0055] Example 1
[0056] 1) Preparation of composite salt: Add 28.75 g (0.208 mol) potassium carbonate (particle size 30-200 μm) and 5.1 g (0.052 mol) potassium acetate (particle size 100-300 μm) into a high-speed crusher, mix at high speed for 3 minutes and then pour out for use.
[0057] 2) Polymerization reaction: 45.66g (0.2mol) bisphenol A, 57.43g (0.2mol) 4,4'-dichlorodiphenyl sulfone, 16.925g composite salt (50%), and 164.2g NMP were added to a 500mL three-necked flask continuously supplied with nitrogen. After the addition, the nitrogen was stopped and the system was sealed, and the nitrogen was replaced 3 times. Then, the system was heated to 190°C in a nitrogen atmosphere to discharge NMP and the water generated by the reaction in the form of an azeotrope. The water separation was stopped until the water content in the system was less than 1000ppm. Then, the remaining composite salt was added to the reaction solution, and the reaction solution temperature was increased to 200°C to continue the reaction. After the solution viscosity reached the standard, it was poured into deionized water for precipitation. The precipitated polymer was crushed, washed, dried, and extruded to obtain polysulfone resin particles, which were recorded as PSU-1.
[0058] Example 2
[0059] 1) Composite salt preparation: The composite salt configuration is consistent with that in Example 1.
[0060] 2) Polymerization reaction: Except that the polymerization system solvent was changed from NMP to DMAC, the rest of the preparation method was the same as that in Example 1, and the obtained polysulfone resin particles were recorded as PSU-2.
[0061] Example 3
[0062] 1) Preparation of composite salt: Add 23.22 g (0.168 mol) of potassium carbonate (particle size 30-200 μm) and 4.12 g (0.042 mol) of potassium acetate (particle size 50-300 μm) into a high-speed crusher, mix at high speed for 3 minutes, and then pour out for use.
[0063] 2) Polymerization reaction: except that the amount of composite salt was changed to the amount prepared in 1), the rest of the preparation method was the same as that in Example 1, and the obtained polysulfone resin particles were recorded as PSU-3.
[0064] Example 4
[0065] 1) Preparation of composite salt: Add 33.17 g (0.24 mol) of potassium carbonate (particle size 30-200 microns) and 5.89 g (0.06 mol) of potassium acetate (particle size 50-300 microns) into a high-speed crusher, mix at high speed for 3 minutes, and then pour out for use.
[0066] 2) Polymerization reaction: except that the amount of composite salt was changed to the amount prepared in 1), the rest of the preparation method was the same as that in Example 1, and the obtained polysulfone resin particles were recorded as PSU-4.
[0067] Example 5
[0068] 1) Preparation of composite salt: Add 34.14 g (0.247 mol) potassium carbonate (particle size 30-200 μm) and 1.28 g (0.013 mol) potassium acetate (particle size 100-300 μm) into a high-speed crusher, mix at high speed for 3 minutes and then pour out for use.
[0069] 2) Polymerization reaction: except that the amount of composite salt was changed to the amount prepared in 1), the rest of the preparation method was the same as that in Example 1, and the obtained polysulfone resin particles were recorded as PSU-5.
[0070] Example 6
[0071] 1) Preparation of composite salt: Add 25.15 g (0.182 mol) potassium carbonate (particle size 30-200 microns) and 7.65 g (0.078 mol) potassium acetate (particle size 100-300 microns) into a high-speed crusher, mix at high speed for 3 minutes, and then pour out for use.
[0072] 2) Polymerization reaction: In the polymerization part, except that the amount of composite salt was changed to the amount prepared in 1), the rest of the preparation method was the same as that in Example 1, and the obtained polysulfone resin particles were recorded as PSU-6.
[0073] Example 7
[0074] 1) Preparation of composite salt: Add 17.97 g (0.13 mol) potassium carbonate (particle size 30-200 microns) and 12.75 g (0.13 mol) potassium acetate (particle size 100-300 microns) into a high-speed crusher, mix at high speed for 3 minutes, and then pour out for use.
[0075] 2) Polymerization reaction: In the polymerization part, except that the amount of composite salt was changed to the amount prepared in 1), the rest of the preparation method was the same as that in Example 1, and the obtained polysulfone resin particles were recorded as PSU-7.
[0076] Example 8
[0077] 1) The preparation of the composite salt is consistent with that in Example 1.
[0078] 2) Polymerization Reaction The preparation method is the same as that in Example 1 except that the amount of the composite salt in the first step is changed to 30% of the amount prepared in 1). The obtained polysulfone resin particles are recorded as PSU-8.
[0079] Example 9
[0080] 1) The preparation of the composite salt is consistent with that in Example 1.
[0081] 2) Polymerization Reaction The preparation method is the same as that in Example 1 except that the amount of the composite salt in the first step is changed to 70% of the amount prepared in 1). The obtained polysulfone resin particles are recorded as PSU-9.
[0082] Comparative Example 1
[0083] To a 500mL three-necked flask continuously supplied with nitrogen, 45.66g (0.2mol) bisphenol A, 57.43g (0.2mol) 4,4'-dichlorodiphenyl sulfone, 35.93g potassium carbonate (0.26mol), and 164.2g NMP were added in sequence. After the addition, the nitrogen was stopped and the system was sealed, and the nitrogen was replaced three times. Then, the system was heated to 190°C in a nitrogen atmosphere, and NMP and the water generated by the reaction were discharged in the form of an azeotrope. The water separation was stopped until the water content in the system was less than 1000ppm, and then the temperature of the reaction solution was increased to 200°C to continue the reaction. After the solution viscosity reached the standard, it was poured into deionized water for precipitation. The precipitated polymer was crushed, washed, dried, and extruded to obtain polysulfone resin particles, which were recorded as DPSU-1.
[0084] Comparative Example 2
[0085] 1) Preparation of composite salt: Add 14.37 g (0.104 mol) potassium carbonate (particle size 30-200 microns) and 15.31 g (0.156 mol) potassium acetate (particle size 100-300 microns) into a high-speed crusher, mix at high speed for 3 minutes, and then pour out for use.
[0086] 2) Polymerization reaction: In the polymerization part, except that the compound salt feed amount was changed to the above-mentioned preparation amount, the rest of the preparation method was the same as that in Example 1, and the obtained polysulfone resin particles were recorded as DPSU-2.
[0087] Comparative Example 3
[0088] 1) The preparation of the composite salt is consistent with that in Example 1.
[0089] 2) Polymerization Reaction The preparation method is the same as that in Example 1 except that the amount of the composite salt in the first step is changed to 20% of the amount prepared in 1). The obtained polysulfone resin particles are recorded as DPSU-3.
[0090] The molecular weight, heat-resistant YI value and solution turbidity test results of the polysulfone resins prepared in the above examples and comparative examples are shown in the following table:
[0091]
[0092]
[0093] From the above data comparison, it can be seen that the polysulfone resin prepared by the present invention has lower oligomer content and polymer content, and the polymer has better heat resistance, yellowing resistance and degradation resistance, and the organic solution containing the polysulfone resin prepared by the present invention has better stability.
[0094] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A polysulfone resin, characterized in that The invention relates to a polyisocyanate having a para-dihalogenated diphenyl sulfone compound of formula (I) and a bisphenol A-type compound of formula (II) as raw material monomers, and is prepared by a nucleophilic substitution method. The polyisocyanate has the following structural characteristics: A is the logarithmic value log(M) of the molecular weight M, and B is the concentration fraction C obtained by differentiating the logarithmic value log(M) of the molecular weight. Then, in a molecular weight distribution curve with A as the horizontal coordinate and B as the vertical coordinate, (1) the value of B reaches a maximum in the range of 4.5≤A≤5.5, and (2) in the molecular weight distribution curve, the value obtained by integrating the value of B in the range of A≤A-0.8 and A≥A+0.3 is 3%-10% relative to the value obtained by integrating the value of B in the entire range of A. Wherein, R1, R2, R3, R4, R5, R6, R7, and R8 are independently selected from H, halogen, C1-C 10 Alkyl, C5-C6 cycloalkyl or C6-C 10 Any one of the aryl groups; X1 and X2 are selected from the same halogen.
2. The polysulfone resin according to claim 1, characterized in that The structural formulas of the para-dihalogen diphenyl sulfone compound of formula (I) and the bisphenol A type compound of formula (II) are respectively: Preferably, the mass content of the cyclic dimer of the structure of formula (V) in the polysulfone resin is less than 1.2%.
3. The method for preparing a polysulfone resin according to claim 1 or 2, characterized in that: The following steps are involved: (1) Preparation of composite inorganic salts: Weigh potassium acetate and other inorganic salts, crush them at high speed, mix them evenly and set aside; (2) Polymerization reaction: first, the polymerization raw material monomer, organic solvent and part of the composite inorganic salt are added to the reaction kettle, and after nitrogen replacement, the temperature is raised to the boiling point of the solvent to separate water; as the salt formation reaction and water separation continue, the water content in the distilled liquid continues to decrease. When the water content in the system reaches the standard, the remaining composite inorganic salt is added and the reaction is continued. When the solution viscosity reaches the standard, the temperature is lowered to stop the reaction; (3) Post-treatment: The polymer solution is diluted and filtered, and the filtrate is precipitated and crushed. Finally, the crushed powder is washed and dried to obtain the polysulfone resin.
4. The method for preparing a polysulfone resin according to claim 3, characterized in that: In the preparation of the composite inorganic salt, other types of inorganic salts are selected from one or more of K2CO3, KHCO3, Na2CO3 or NaHCO3; Preferably, in the composite inorganic salt, potassium acetate accounts for 5% to 50% of the total molar amount of the inorganic salt, preferably 10% to 40%, and more preferably 15% to 30%.
5. The method for preparing a polysulfone resin according to claim 3 or 4, characterized in that: In the preparation of the composite inorganic salt, after being crushed by a high-speed pulverizer, the particle size D50 of the composite inorganic salt is below 100 μm, preferably below 70 μm, and more preferably below 50 μm.
6. The method for preparing a polysulfone resin according to claim 3, characterized in that: In the polymerization reaction, the molar ratio of the para-dihalogen diphenyl sulfone compound of formula (I) to the bisphenol A compound of formula (II) in the polymerization raw monomer is 1:(0.95-1.05), preferably 1:(0.97-1.03), and more preferably 1:(0.98-1.02).
7. The method for preparing a polysulfone resin according to claim 3, characterized in that: In the polymerization reaction, the organic solvent is one or more of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide or sulfolane; Preferably, the mass fraction of the organic solvent in the polymerization reaction system is 20% to 60%, preferably 25% to 55%, and more preferably 30% to 50%.
8. The method for preparing a polysulfone resin according to claim 3, characterized in that: In the polymerization reaction, the molar amount of the composite inorganic salt used is 100% to 150% of the molar amount of the dihalogen diphenyl sulfone compound monomer, preferably 110% to 140%, more preferably 120% to 130%; Preferably, in the polymerization reaction, the part of the composite inorganic salt accounts for 30% to 70% of the total mass of the composite inorganic salt, preferably 40% to 65%, more preferably 50% to 60%.
9. The method for preparing a polysulfone resin according to claim 3, characterized in that: In the polymerization reaction, the water content in the distillate is 2000 ppm or less, preferably 1500 ppm or less, and more preferably 1000 ppm or less, which is regarded as the water content in the system meeting the standard.
10. Use of the polysulfone resin according to claim 1 or 2 or the polysulfone resin prepared by the preparation method according to any one of claims 3 to 9 in the fields of squirrel cages, flow meters, hydrogen electrolyzers and hollow fiber membranes.
Citation Information
Patent Citations
Aromatic polyether sulfone having hydroxyphenyl end group and method for producing the same
CN101848956A
Preparation method of polysulfone resin material with low cyclic dimer content
CN111253574A
Method for preparing polysulfone resin through combination of nucleophilic polycondensation and anionic ring-opening polymerization
CN116003796A
Polysulfone films
US20010056175A1
Method for producing hydroxyl-terminated polysulfone
WO2012133640A1